Evaluation of sunscreening and antibacterial activity of the cream containing pomegranate peel extract - B. THOLKAPPIYAN; A. CHARLES MARTIN; G. RAWOOF KHAN; N. NARAYANAN; M. PRABHU; P. VANI (International Journal of Pharma and Bio Sciences, 2010)
Cosmetic products are formulated for application on the body for the purpose of cleansing, beautifying, or altering appearance and enhancing the beauty. The ozone layer in the stratosphere practically prevents the UV photons from reaching the earth’s surface of concern for human skin damage, therefore, only UV-B and UV-A radiation are relevant. In the present study an attempt has been made to formulate a cream containing alcoholic extract of pomegranate peel extract. The quantity control parameters of Punica granatum were performed as per WHO guidelines. The cream was formulated using pomegranate peel extract in two concentrations (10% and 25%). The UV analysis of different concentrations of prepared creams are done along with standard cream which has TiO2 as the active ingredient. The extraction of peel was carried out by continuous hot percolation using Soxhlet apparatus and the phytochemical screening revealed the presence of flavanoids, tannins, anthocyanins and polyphenolic compounds. The evaluation of antibacterial activity is done by cup and plate technique using ethanolic extract of pomegranate peel against Staphylococcus aureus, Pseudomonas aeruginosa. The results showed that the ethanolic extract of pomegranate peel has very good sensitivity against both gram positive and gram negative organism.